Atlas of the Food System of Lisbon Region: Urban forms of the everyday living - Marat-Mendes, T.; Lopes, S. S.; Borges, J.C.; d'Almeida, P. Bento (XXIX Conference of the International Seminar on Urban Form (ISUF 2022), 2022)
The world is changing, and urban agendas are struggling with conventional planning paradigms and urban form solutions, to improve environmental, economic, and social conditions in cities, while responding to society’s request for sustainability. ‘Transforming our world: The 2030 Agenda for sustainable development’, published by the United Nations, calls for changes in all aspects of life, including on the way humanity relates to the planet. Urban form, as the physical creation that results from specific humanity needs (for shelter, mobility, work, transform, etc.) assembles an accumulation of material stocks that are directly implicated in such agenda. Urban history has registered many former urban form solutions that have already disappeared, declined, altered, or even abandoned, as these are no longer need by society. Others have proved to resist longer or were subject of continuous restructuration, either adapted to accommodate new society uses, tastes or functions. Advances on technology, design, humanity needs and scientifical knowledge have also allowed society to shape new urban forms. Altogether, past, and present urban forms constitute an immense and inestimable repository of humanity physical creation of great complexity. At a time when humanity is calling for a sustainability change, while enquiring urban form itself in such process, it is important for urban morphologists to update and revise the concepts and definitions that are being purposed at our very own time. This presentation aims to introduce an ongoing taskforce that aims to compile such concepts and definitions of urban form, while exposing its methodological approach and some ongoing conclusions.